Descartes-Agonistes - Schuster, John. author. aut Link
XX, 632 p.
Keywords: This book reconstructs key aspects of the early career of Descartes from 1618 to 1633; that is, up through the point of his composing his first system of natural philosophy, Le Monde, in 1629-33. It focuses upon the overlapping and intertwined development of Descartes’ projects in physico-mathematics, analytical mathematics, universal method, and, finally, systematic corpuscular-mechanical natural philosophy. The concern is not simply with the conceptual and technical aspects of these projects; but, with Descartes’ agendas within them and his construction and presentation of his intellectual identity in relation to them. Descartes’ technical projects, agendas and senses of identity shifted over time, entangled and displayed great successes and deep failures, as he morphed from a mathematically competent, Jesuit trained graduate in neo-Scholastic Aristotelianism to aspiring prophet of a systematised corpuscular-mechanism, passing through stages of being a committed physico-mathematicus, advocate of a putative ‘universal mathematics’, and projector of a grand methodological dream. In all three dimensions—projects, agendas and identity concerns—the young Descartes struggled and contended, with himself and with real or virtual peers and competitors, hence the title ‘Descartes-Agonistes’. .